Análise dos teores de flúor em municípios com e sem fluoretação das águas de abastecimento público - Toledo, Tássila Franco de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The fluoridation of drinking water is considered a public health measure, which is effective and wide-ranging and also helps controling and preventing dental caries. Monitoring systems of the fluoride levels in public water supplies are essential to adapt the contents at intervals that provide the greatest benefit in relation to the prevention of caries and lower risk of developing dental fluorosis. The purpose of this study was to analyze the levels of fluoride in public water supplies, distributed by 3 cities of water treatment supplies, with and without fluoride located in the northwest of the state of São Paulo. Three points were defined for each source of public municipal water supply. Water samples were collected monthly and analyzed in the Research Laboratory of the Center for Public Health (NEPESCO), Graduate Program in Public Health, School of Dentistry of Araçatuba (UNESP). During a period of 88 months of 2974 samples, the levels of fluoride in 65.23% (n = 970) had levels of fluoride between 0.55 and 0.84 mg F / L,; 13.38% (n = 199) had a content below 0.55 mg F / L and 21.38% (n = 318) had fluoride levels above 0.84 mg F / L. Among the municipalities that did not add fluoride, one of the control samples had shown values less than 0.55 mg F / L and the other with values above 0.84 mg F / L, providing the maximum benefit, related to dental caries and it also had a moderate cost as high as dental fluorosis. It stands out that it's necessary to analyze the water distribution networks and develop procedures for dilution and mixing to improve the use of natural fluoride in deepwater wells, aiming to achieve the desired level of fluoride. It was found that in cities that added artificially ion in water, the process was continuous and within the recommended parameters, considering then...

A fluoretação das águas de abastecimento é considerada uma medida de saúde pública eficaz e de grande abrangência auxiliando no controle e prevenção da cárie dentaria. Sistemas de monitoramento dos teores de fluoreto nas águas de abastecimento público são imprescindíveis para adequação dos níveis em intervalos que proporcionam o maior benefício em relação à prevenção da cárie e o menor risco de desenvolvimento da fluorose dentária. O objetivo deste trabalho foi analisar os teores do íon flúor presente nas águas de abastecimento público distribuídas pela estação de tratamento de 3 municípios com fluoretação e 3 sem a adição do fluoreto localizados na região noroeste do estado de São Paulo. Três pontos de coleta foram definidos para cada fonte de abastecimento de água pública municipal. Amostras de água foram coletadas mensalmente e analisadas no Laboratório de Pesquisa do Núcleo de Saúde Coletiva (NEPESCO), Programa de Pós-Graduação em Odontologia Preventiva e Social, Faculdade de Odontologia de Araçatuba (UNESP). Durante um período de 88 meses das 2974 amostras analisadas, os níveis de íon flúor de 65,23% (n =970) apresentaram níveis de fluor entre 0,55 e 0,84 mg F / L; 13,38% (n = 199) apresentaram teores abaixo de 0,55 mg F/L; e 21,38% (n= 318) apresentaram níveis de flúor acima de 0.84 mg de F/L. Dentre os municípios que não adicionavam fluoreto, um deles apresentou amostras controles abaixo de 0,55 mg F/L e outro com valores acima de 0,84mg F/L, tendo este último proporcionado benefício máximo em relação a cárie dentária e risco moderado a alto quanto a fluorose dentária. Destaca-se, então, a necessidade de analisar as redes de distribuição de água e desenvolver procedimentos de diluição e mistura para...
Keywords: Fluoretação; Água; Flúor; Saúde bucal; Fluoridation